2019
DOI: 10.1088/1674-1056/28/7/074201
|View full text |Cite
|
Sign up to set email alerts
|

Design of an augmented reality display based on polarization grating*

Abstract: A new optical system for an augmented reality (AR) display is proposed in this paper. The optical system mainly includes a ray deflector, coupling input grating, optical waveguide, and coupling output grating. Both the ray deflector and the coupling input grating are designed based on the diffraction characteristics of the polarization grating, and the coupling output grating is the Bragg reflection grating. Compared with other AR schemes, this AR optical system not only reduces the number of projections from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Lin et al designed and experimentally demonstrated a polarization multiplexing holographic memory with an increased storage capacity using a circular polarization recording configuration [72]. Similarly, polarization holographic gratings were applied for polarization multichannel multiplexing, vector beam storage, and fabrication of polarization multiplexing diffracting optical elements [73], self-interference incoherent digital holography [74,75], virtual reality displays [76,77], and also 4G optical elements with spatially modulated birefringence across the surface [78,79]. Yang et al and Xia et al applied the diffraction characteristics of anisotropic gratings to demonstrate logic operations using Boolean algebra for all-optical diffraction elements using an azo-dye doped polymer film [80,81].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al designed and experimentally demonstrated a polarization multiplexing holographic memory with an increased storage capacity using a circular polarization recording configuration [72]. Similarly, polarization holographic gratings were applied for polarization multichannel multiplexing, vector beam storage, and fabrication of polarization multiplexing diffracting optical elements [73], self-interference incoherent digital holography [74,75], virtual reality displays [76,77], and also 4G optical elements with spatially modulated birefringence across the surface [78,79]. Yang et al and Xia et al applied the diffraction characteristics of anisotropic gratings to demonstrate logic operations using Boolean algebra for all-optical diffraction elements using an azo-dye doped polymer film [80,81].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the optical loss of the dielectric nanomaterial is much lower than that of metal. Dielectric metasurfaces have been proposed as an alternative route, where the ohmic loss could be avoided to improve the efficiency of PSHE [33][34][35][36][37]. However, how to achieve an enhanced PSHE in the high-frequency visible light region and broaden the working bandwidth is still a challenge.…”
Section: Introductionmentioning
confidence: 99%